Urinary B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL): potential biomarkers of active lupus nephritis. (5th December 2016) - Phatak, S; Chaurasia, S; Mishra, S K; Gupta, R; Agrawal, V; Aggarwal, A; Misra, R
Summary: B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) help in B cell activation, maintenance and plasma cell survival. B cell infiltration has been demonstrated in kidneys of patients with lupus nephritis (LN). Serum levels of BAFF and APRIL have shown inconsistent relationships with lupus disease activity. We evaluated urinary levels of BAFF and APRIL as biomarker for LN. Thirty-six patients with proliferative lupus nephritis (AN), 10 with active lupus without nephritis (AL) and 15 healthy controls (HC) were studied. APRIL and BAFF levels were measured in both serum and urine using enzyme-linked immunosorbent assay (ELISA). Urine levels were normalized for urinary creatinine excretion. Urine levels were correlated with conventional disease activity markers and histology. Levels were reassessed in 20 AN patients at 6 months after treatment with cyclophosphamide. Urinary APRIL (uAPRIL) and BAFF (uBAFF) levels were raised significantly in AN. uAPRIL, but not uBAFF, correlated moderately with renal Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) in AN ( r  = 0·36, P  < 0·05). On receiver operator curve (ROC) analysis, uBAFF and uAPRIL showed an area under the curve (AUC) of 0·825 and 0·781, respectively, in differentiating between nephritis and non-nephritis, which performed better than low C3, C4 and raised anti-dsDNA antibodies. There was no correlation of serum levels with uBAFF ( r  = 0·187, P  = 0·261) and uAPRIL ( r  = 0·114, P  = 0·494). uAPRIL levels reduced after treatment (mean 125 pg/mg to 36 pg/mg, P  < 0·05). uBAFF levels reduced in 16 responders while two of four non-responders had increase in levels. Thus, uBAFF and uAPRIL are potential biomarkers of proliferative lupus nephritis. Graphical Abstract: